Dampak Penggunaan Media Sosial Terhadap Perkembangan Dimensi Keberagamaan Remaja Perspektif Psikologi Agama - Polem, Muhammad (Lembaga Penelitian Dan Pengabdian Masyarakat Stai Brebes, 2024)
The development of social media is like a double-edged knife, it can hurt or provide benefits for its users. The purpose of this study is to analyze how the impact of social media use on the development of the dimensions of adolescent religiosity from the perspective of the psychology of religion. The research method uses a qualitative approach with a literature study method. The data source is secondary data. Data collection techniques include collecting, editing, categorizing, and summarizing data. While data analysis by analyzing the content in depth. The results revealed that the use of social media can have a positive and negative impact on five aspects of the development of the dimensions of religiousness in adolescents. For example, in the worship dimension, adolescents can utilize social media to disseminate useful information and learn about how to worship properly according to Sharia. However, if they are not wise, teenagers will actually get carried away and forget about time and then leave their worship such as prayer, because they are engrossed in surfing social media. The conclusion of this study states that the development of social media must be accompanied by a wise attitude of its users, especially teenagers who psychologically tend to be easily influenced and follow trends that are sometimes not following the values of Islamic teachings. The implications of the research hopefully can be useful for researchers and readers, especially parents and teachers who must be extra in guiding and fostering the teenagers they have, so that they are always in a good moral corridor.